Uma leitura etnográfica dos mulçumano da mesquita Luz da Fé em Campo Grande - Desafios para vivenciar o Ramadan - Diogenes Braga Ramos (2021)
This research aims to analyze the Ramadan rite at the Campo Grande mosque, to understand how the rite is established and, in addition, how it affects the community, based on fasting practices. For the research, fieldwork was carried out at the mosque, dialogues and conversations with some people who are members of the community and somehow experienced Ramadan in this pandemic year. For this, the rite in general was observed from the classics of Anthropology that made me argue that the collective memory established by the Ramadan rite gives meaning and unity for the members of the mosque to participate and live their faith in Islam. This research demonstrates that there is diversity in Islam and that each community, and each Muslim exercises their faith based on the pillars of Islam, including Ramadan.